Use of Aymara in the Chile, Peru, and Bolivia Frontiers: A Micro-Sociolinguistic Analysis - Mamani Morales, Juan Carlos (Íkala, Revista de Lenguaje y Cultura, 2023)
The Aymara language (AL) is one of the most important languages in the central Andean region. However, there are few studies on its use from a microsociolinguistic approach. This paper aims to analyze the use of the Aymara language in six commercial speech events in a tri-border context involving Aymara speakers from Chile, Peru, and Bolivia. The conversations that happened within these events were collected through audio recordings and written records in a qualitative ethnographic intervention in the so-called three-part fair or “Feria Tripartita” (FT), a commercial event that occurs weekly in the three-border area. The analysis is based on ethnography of communication, conversational analysis, and interactional sociolinguistics. Drawing on this analytical framework, the use of the AL that is manifested there shows code-switching with Spanish, both inter- and intra-orally, along with a series of interlinguistic phenomena, such as the presence of a series of Spanish lexical bases with Aymara suffixation, and the use of unnecessary Spanish loans. Thus the FT, in spite of being an Aymara space that conforms a bilingual speaking community, is a space of influence of the Castilian language, which structurally affects the use of the AL.